Understanding accounting information by internal users: A case study at a brazilian public university - Alves, Maria Arlete Ferreira; Gouveia , Tânia Maria de Oliveira Almeida; Oliveira , Carlyle Tadeu Falcão de (Seven Editora, 2023)
Objective: To examine the understanding of accounting information and its relevance in the decision-making process from the perspective of internal users in the public sector. Method: A case study at the Federal Rural University of Rio de Janeiro (UFRRJ). Data was collected through semi-structured interviews, and the analysis was based on the content analysis method. Results: Budgetary information is the most prevalent and relevant in the decision-making process. Accounting information related to assets is less utilized and more relevant for meeting external requirements. The main factor influencing managers’ understanding is the highly technical language of accounting. Originality/Relevance: Understanding the factors that influence comprehension of accounting information contributes to improving communication between accounting professionals and managers, ensuring that this information is consistently present and appropriately used in decision-making. Theoretical/Methodological Contributions: Considering that accounting is a type of language, the findings of this research indicate that, based on the theory of semiotics, the syntactic aspect is understood by managers. However, the semantic and pragmatic aspects, which are part of the communicative relationship, are not effectively achieved. It is in these dimensions that a satisfactory level of comprehension occurs, representing the accounting events to their users and influencing the quality of managers’ actions and decisions. DOI:https://doi.org/10.56238/sevened2023.006-044